Single-cell profiling delineates the tumor microenvironment and immunological networks in patient-derived uterine leiomyosarcoma - Guo, Yi; Shen, Dongsheng; Xiao, Yuhang; Wu, Chenghao; Chen, Meiyi; Yang, Lina; Li, Huaifang; Tong, Xiaowen; Chen, Rujun; Li, Fang (Frontiers in Immunology, 2025)
BackgroundUterine leiomyosarcoma (ULSA) is a highly aggressive gynecologic malignancy characterized by early metastasis, profound immunosuppression, and resistance to conventional therapies, including immune checkpoint blockade (ICB). The intricate tumor microenvironment (TME) and cellular heterogeneity driving its progression and therapy resistance remain poorly defined.MethodsWe performed single-cell RNA sequencing (scRNA-seq) on metastatic lesions (pelvic cavity, rectum, peritoneum, bladder) from a treatment-naïve ULSA patient and compared them to normal uterine myometrium, MMM (n=5). Integrated analyses included cellular composition mapping, copy number variation (CNV) assessment, pseudotemporal trajectory reconstruction, cell-cell communication inference, functional enrichment, and validation via multiplex immunofluorescence (mpIF). Survival correlations were assessed using the TCGA-SARC cohort.ResultsIn this study, the main finding is that the tumor microenvironment (TME) has a strong immunosuppressive effect. Firstly, its characteristic is exhausted CD8+T cells. This study found that as time progresses, the initial cell markers (CCR7, MAL) gradually disappear, while the exhaustion markers (LAG3, HAVCR2, TIGIT) are enriched. This is associated with poor prognosis. Secondly, the M2-polarized macrophages are mainly composed of M2-like tumor-associated macrophages (TAMs) with tumor-promoting characteristics (CD163, FTH1, FTL, TIMP1), and there is a polarization from M1 to M2. Finally, the immature, tumor-promoting N2 neutrophils (CD15+EDARADD+) enriched in the metastatic foci are associated with poor prognosis. The cell communication involves the interaction of MIF-(CD74+CD44) between T/B cells, as well as the role of the CXCL8 signaling axis in promoting angiogenesis, TAM polarization, and immunosuppression.ConclusionFor the first time, a comprehensive single-cell map of ULSA was constructed, depicting a metastasis-susceptible cell subset (U11-EDARADD) and an extremely immunosuppressed tumor microenvironment dominated by depleted CD8+T cells, M2 macrophages and N2 neutrophils. These features shed light on the underlying mechanisms of chemotherapy resistance and immunotherapy failure. The biomarkers identified here (EDARADD, CLDN10, TMIGD2) as well as the dysregulated pathways (TGF-β, angiogenesis, MIF signaling) provide possible targets for future development of combined immunotherapy strategies against this deadly disease.